Visible and Near-infrared Laboratory Demonstration of a Simplified Pyramid Wavefront Sensor. (14th March 2019) - Lozi, Julien; Jovanovic, Nemanja; Guyon, Olivier; Chun, Mark; Jacobson, Shane; Goebel, Sean; Martinache, Frantz
Abstract: Wavefront sensing and control are important for enabling one of the key advantages of using large apertures, namely higher angular resolution. Pyramid wavefront sensors are becoming commonplace in new instrument designs owing to their superior sensitivity. However, one remaining roadblock to their widespread use is the fabrication of the pyramidal optic. This complex optic is challenging to fabricate due to the pyramid tip, where four planes need to intersect at a single point. Thus far, only a handful of these have been produced due to the low yields and long lead times. To address this, we present an alternative implementation of the pyramid wavefront sensor which relies instead on two roof prisms. Such prisms are easy and inexpensive to source. We demonstrate the successful operation of the roof prism pyramid wavefront sensor on an 8 m class telescope, at visible and near-infrared wavelengths, for the first time using a SAPHIRA HgCdTe detector without modulation for a laboratory demonstration, and elucidate how this sensor can be used more widely on wavefront control test benches and instruments.